Turnover in Child Care Arrangements - Blau, David M.; Robins, Philip K. (The Review of Economics and Statistics, 1991)
This paper analyzes changes in child-care arrangements of a sample of children from the Youth Cohort of the National Longitudinal Surveys over the first three years of life. The analysis indicates that turnover in child-care arrangements is surprisingly low among this sample and is more common among families of higher socioeconomic status. Child-care turnover is positively correlated with mothers' employment turnover, but is not correlated with changes in mothers' marital status or additional births. Turnover in child-care arrangements is highly correlated over time, due mainly to the effects of observed variables and unobserved characteristics of the mothers. Copyright 1991 by MIT Press.